MATHEMATICAL CONCEPTS ABILITY IN SPLDV MATERIAL BASED ON APOS THEORY STAGES VIEWED FROM LEARNING STYLES - Elisabet Lerebulan; Mesak Ratuanik (JURNAL EDUSCIENCE, 2023)
This study aims to determine the ability of mathematical concepts in the material system of two-variable linear equations (SPLDV) based on the stages of APOS theory in terms of the learning styles. The type of research used in this research is qualitative research. The subjects in this study were 32 students of class X SMA Negeri 10 Tanimbar Islands Regency. The instrument used in this research is a) observation. Observation aims to observe student activity in understanding mathematical concepts in SPLDV material in applying APOS theory in terms of student learning styles, b) interviews. Interview sheets were used to obtain information related to understanding mathematical concepts in SPLDV material in applying APOS theory in terms of student learning styles c) Tests The test sheets in this study were given to students after being given mathematics learning with an understanding of mathematical concepts in SPLDV material in applying APOS theory in terms of student learning styles. The results of this study indicate that the APOS theory as an elaboration of mental construction from actions (actions), processes (processes), objects (objects), schemes (schema) improves students with visual learning styles, auditory learning styles and kinesthetic learning styles can improve students' abilities. mathematical concepts in the material system of two-variable linear equations (SPLDV).Keywords: APOS Theory, Learning Styles and SPLDV Concepts.AbstrakPenelitian ini bertujuan untuk mengetahui kemampuan konsep matematika pada materi sistem persamaan linear dua variabel (SPLDV) berdasarkan tahapan teori APOS ditinjau dari gaya belajar. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian kualitatif. Subjek dalam penelitian ini adalah siswa kelas X SMA Negeri 10 Kabupaten Kepulauan Tanimbar yang berjumlahÂ  32 siswa. Instrumen yang digunakan dalam penelitian ini adalah a) observasi. Observasi bertujuan untuk mengamati aktifitas siswa dalam pemahaman konsep matematika pada materi SPLDV dalam menerapkan teori APOS ditinjau dari gaya belajar siswa, b) wawancara. Lembar wawancara digunakan untuk mendapatkan informasi yang berkaitan dengan pemahaman konsep matematika pada materi SPLDV dalam menerapkan teori APOS ditinjau dari gaya belajar siswa c) Tes Lembar tes dalam penelitian ini diberikan kepada siswa sesudah diberikan pembelajaran matematika dengan pemahaman konsep matematika pada materi SPLDV dalam menerapkan teori APOS ditinjau dari gaya belajar siswa. Hasil penelitian ini menunjukan bahwa teori APOS sebagai suatu elaborasi tentang konstruksi mental dari aksi (actions), proses (processes), objek (objects), skema (schema) meningkatkan siswa dengan gaya belajar visual, gaya belajar auditorial dan gaya belajar kinestetik dapat meningkatkan kemampuan konsep matematika pada materi sistem persamaan linear dua variabel (SPLDV). Kata Kunci : Teori APOS, Gaya Belajar dan Konsep SPLDV.